The Concept of Happiness in the Perspective of the Qur'an and its Relevance to Modern Muslim Life - Mifta, Miftakhul Khoiriyah; Miftarah Ainul Mufid; Wiwin Ainis Rohtih (Jurnal Semiotika-Q, 2025)
Happiness is an aspect of human life that is the main goal in various aspects of life. However, the concept of happiness in modern Muslim life is being challenged due to changing times, technological advancements, and changes in people's mindsets. This study aims to examine the concept of happiness from the Qur'anic perspective using the maudhu'i (thematic) tafsir method and how the concept is applied in modern Muslim life. This research uses a qualitative approach with a library research method that collects various sources of tafsir and other supporting literature to understand the concept of happiness in Islam. The results show that the Qur'an describes happiness not only as material or worldly satisfaction, but also as peace of mind, piety, patience, and a balance between life in this world and life in the hereafter. The concept of happiness in Islam emphasizes the importance of remembering Allah, doing good deeds, and having an attitude of qana'ah and tawakkal. In the face of the challenges of modern life, such as materialism, hedonisme, and spiritual crisis, Islam offers solutions through a spiritual approach and life balance. This research provides insight into true happiness in modern Muslim life, which comes not only from external factors, but also from a deep understanding of Islamic teachings and their application in daily life. Happiness is an aspect of human life that is the main goal in various aspects of life. However, the concept of happiness in modern Muslim life is being challenged due to changing times, technological advancements, and changes in people's mindsets. This study aims to examine the concept of happiness from the Qur'anic perspective using the maudhu'i (thematic) tafsir method and how the concept is applied in modern Muslim life. This research uses a qualitative approach with a library research method that collects various sources of tafsir and other supporting literature to understand the concept of happiness in Islam. The results show that the Qur'an describes happiness not only as material or worldly satisfaction, but also as peace of mind, piety, patience, and a balance between life in this world and life in the hereafter. The concept of happiness in Islam emphasizes the importance of remembering Allah, doing good deeds, and having an attitude of qana'ah and tawakkal. In the face of the challenges of modern life, such as materialism, hedonisme, and spiritual crisis, Islam offers solutions through a spiritual approach and life balance. This research provides insight into true happiness in modern Muslim life, which comes not only from external factors, but also from a deep understanding of Islamic teachings and their application in daily life.